O teatro de bonecos popular em sala de aula: ressignificando saberes no ensino de teatro - Oliveira, Wandeson Alves de (2025)
This research aims to experiment with and reflect on methodological approaches to Theater Education that can contribute to the emancipation of students' knowledge through the practice of the Traditional Puppet Theater of the Northeast. It is a case study developed during the third academic term at Escola Estadual Belém Câmara, a public school located in the Cidade da Esperança neighborhood, in the western zone of Natal/RN, with sixth-grade students from the final years of elementary school. As methodological procedures, puppet-making workshops were conducted using recycled materials. The entire process was documented through photos and videos, as well as notes in a logbook. The theoretical references for this study included Sandro Roberto dos Santos (2022), André Carrico (2016, 2017), Zildalte Ramos de Macêdo (2015), José Sávio de Oliveira Araújo (2015), Canclini (2015), Graça Cavalcanti (2011), Ana Mae Barbosa (2010), Paulo Freire (1996), Ana Maria Amaral (1996), Fernando Augusto Gonçalves Santos (1979), Hermílio Borba Filho (1969), and José Jorge de Carvalho (1991). This research provided an accessible and meaningful artistic experience, strengthening the cultural identity of the sixth-grade students at the public school. The Traditional Puppet Theater of the Northeast served as a tool for expression and learning, allowing students to explore their social realities through art.